Expressive writing during the COVID-19 pandemic: themes of mixed expressive writing - Hao Yue Tay; Chengen Yu; Chen Sung Wong; Kususanto Ditto Prihadi (International Journal of Public Health Science (IJPHS), 2022)
In order to curb the depression levels among youth during the coronavirus disease 2019 (COVID-19) outbreak, we examined the recurrent themes of mixed expressive writing among undergraduates during the pandemic. Previous quantitative studies had emphasized on the effectiveness of expressive writing in reducing depressive symptoms, however, less qualitative studies were conducted in evaluating the content within people’s writings. As the pandemic had caused major disruptions among people, we implemented mixed expressive writing in capturing both positive and negative experiences during the pandemic. Ten participants were recruited to perform mixed expressive writing twice per week, for four consecutive weeks. Thematic analysis was used in analyzing their writings and forming the emerged themes. Five themes were formed, which included ‘school’, ‘relationships’, ‘reflection’, ‘work’, and “random incidents’. Future research should examine the effectiveness of expressive writing in writing specific themes on improving its respective psychological constructs.